Human and technical dimensions of potato integrated pest management using farmer field schools: International Potato Center and partners’ experience with potato late blight management - Ortíz, O.; Nelson, R.; Olanya, M.; Thiele, Graham; Orrego, R.; Pradel, W.; Kakuhenzire, R.; Woldegiorgis, G.; Gabriel, J.; Vallejo J.; Xie, K. (Oxford University Press, 2019)
In the 1990s, the integrated pest management (IPM) team for potato late blight (IPM-late blight) at the International Potato Center (CIP) began to address the management of this complex potato disease by combining crop protection with social and behavioral sciences. Since the early 2000s, the team has worked with research and development organizations in countries in Asia, sub-Saharan Africa, and South America to develop farmer discovery-based learning methods using farmer field schools (FFS). The principles of late blight control were more visible and understood by farmers when they could test options for managing late blight, particularly new potato clones with resistance to the disease, for themselves. CIP and partners have since adapted an approach combining FFS and participatory research to facilitate farmers’ access to information, knowledge, and technologies. Several manuals to implement FFS-IPM-late blight with farmers were subsequently developed. Results indicated that farmers using this approach learned new knowledge, assessed new potato clones, and changed crop management practices. Hence farmers realized a 32% average increase in potato productivity and income in Peru; similar changes occurred in other countries. The participatory research and training approach had a significant impact beyond IPM-late blight. In Peru and Bolivia, for example, more than 2,000 FFS were implemented between 2005 and 2012 on IPM for potato, other crops (coffee, cocoa, fruit trees), and livestock. In Uganda and Ethiopia, the experience expanded to potato seed management with the formation of seed cooperatives. Lessons have been drawn from this experience.